Quadratus Lumborum Block Versus Perioperative Intravenous Lidocaine for Postoperative Pain Control in Patients Undergoing Laparoscopic Colorectal Surgery: A Prospective, Randomized, Double-blind Controlled Clinical Trial. Issue 5 (November 2018) - Dewinter, Geertrui; Coppens, Steve; Van de Velde, Marc; D'Hoore, André; Wolthuis, Albert; Cuypers, Eva; Rex, Steffen
Abstract : Objective: To investigate the comparative analgesic efficacy of systemic lidocaine and quadratus lumborum (QL) block in laparoscopic colorectal surgery. Background: Although epidural analgesia is the standard to control pain in patients undergoing open colorectal surgery, optimal analgesic management in laparoscopic surgery is less well-defined. There is need for effective and efficient alternatives to epidural analgesia for pain management in patients undergoing laparoscopic colorectal surgery. Methods: A total of 125 patients undergoing laparoscopic colorectal surgery were included in this randomized, double-blind controlled clinical trial. Patients randomly received an intravenous infusion with placebo plus a QL-block with placebo, a QL-block with ropivacaine 0.25% plus intravenous placebo, or intravenous lidocaine plus a QL-block with placebo. Postoperatively, all patients received patient-controlled intravenous anesthesia (PCIA) with morphine. Primary outcome parameter was the opioid consumption during the first 24 hours postoperatively. Secondary endpoints included severity of postoperative pain, time to return of intestinal function, incidence of postoperative nausea and vomiting, and length of hospital stay. Results: The QL-block was not superior to systemic lidocaine for the reduction of morphine requirements in the first 24 hours postoperatively {QL-group: 37.5 (28.4) mg [mean (standard deviation)] vs lidocaine group: 40.2 (25) mg, P = 0.15}. For the majority of secondary outcome parameters, no significant differences were found between the groups. Morphine consumption in the postanesthesia care unit, the number of PCIA-boli demanded by the patient, and the number of PCIA-boli delivered by the PCIA-pump during the first 24 hours postoperatively were lower in the placebo group. Conclusions: In our trial, the QL-block did not provide superior postoperative analgesia when compared to systemic lidocaine in laparoscopic colorectal surgery. Trial registration: Eudra CT: 2014-001499-73; 31/7/2014 Abstract : Supplemental Digital Content is available in the text